Strain and Cracking Surveillance in Engineered Cementitious Composites by Piezoresistive Properties. (18th August 2010) - Yu Yu, Jia Huan Jia Huan; Hou Hou, Tsung Chan Tsung Chan
Abstract : Engineered Cementitious Composites (ECCs) are novel cement-based ultraductile materials which is crack resistant and undergoes strain hardening when loaded in tension. In particular, the material is piezoresistive with changes in electrical resistance correlated with mechanical strain. The unique electrical properties of ECC render them a smart material capable of measuring strain and the evolution of structural damage. In this study, the conductivity of the material prior to loading was quantified. The piezoresistive property of ECC structural specimens are exploited to directly measure levels of cracking pattern and tensile strain. Changes in ECC electrical resistance are measured using a four-probe direct-current (DC) resistance test as specimens are monotonically loaded in tension. The change in piezoresistivity correlates the cracking and strain in the ECC matrix and results in a nonlinear change in the material conductivity.